Pine Bark Compost as A Substrate in Nursery Forest Production - Sánchez, Jesús R. Hernández; Gaytán, Ivan Franco; Ovalle, Ángel Leyva (Journal of Ecohumanism, 2025)
The quality of plants in the nursery depends mainly on the proper selection of the substrate, a factor that directly influences the quality and cost of production. To determine the suitability of organic materials as substrate components, it is essential to know their physical and chemical properties, allowing possible risks and restrictions of use to be assessed. This research determined the effects of incorporating pine bark compost as an alternative substrate in different volumetric proportions on the morphological and physiological indicators of plant quality in five forest species of national productive importance. Moss peat was replaced in two different proportions, compared with a control treatment that represents the most commonly used mixture in domestic containerized production. The results show that using pine bark compost in different proportions presents a viable alternative to the use of moss peat, reducing production costs. The plant quality obtained with pine bark compost at 20% or 50% of the content of the mixture is similar or superior for most morphological and nutritional indices of the species evaluated, establishing this compost as a sustainable and economically advantageous option for the production of forest plants in nurseries.